2022
DOI: 10.1111/lam.13678
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Salmonella Typhimurium, Escherichia coli O157:H7 and Listeria monocytogenes on alfalfa seeds by the combination treatment of vacuumed hydrogen peroxide vapour and vacuumed dry heat

Abstract: Significance and Impact of the Study: Many researchers have focused their attention on developing techniques to reduce seed-borne human pathogens. Dry heat is one of such treatments. However, dry heat treatment usually requires excessive time to reduce pathogens. In our study, a combination treatment using vacuumed hydrogen peroxide vapour and vacuumed dry heat greatly reduced the treatment time required to inactivate food-borne pathogens inoculated on alfalfa seeds. This combination treatment can be used as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The concept of vacuum assisted HPV treatment is not a new one and dates back to a patent issued in 1977 for cold gas sterilization where articles to be sterilized are placed in an enclosure and vacuum is drawn to vaporize the H 2 O 2 solution (Forstrom and Wardle, 1977). Vacuum conditions have been proven to result in greater gas penetration (Fichet et al, 2007) and is reported to accelerate HPV removal (Block, 1991); this could be beneficial for complex device (or material) decontamination/sterilization (McDonnell Frontiers in Food Science and Technology frontiersin.org et al, 2002) or food surfaces with crevices or cracks (Song and Kang, 2022). However, it is important to note that no initial a w values of the black peppercorn were reported, and their methods indicate that inoculated samples were dried for 1 h in a biosafety hood with no mention of the stability of the Salmonella population.…”
Section: Figurementioning
confidence: 99%
“…The concept of vacuum assisted HPV treatment is not a new one and dates back to a patent issued in 1977 for cold gas sterilization where articles to be sterilized are placed in an enclosure and vacuum is drawn to vaporize the H 2 O 2 solution (Forstrom and Wardle, 1977). Vacuum conditions have been proven to result in greater gas penetration (Fichet et al, 2007) and is reported to accelerate HPV removal (Block, 1991); this could be beneficial for complex device (or material) decontamination/sterilization (McDonnell Frontiers in Food Science and Technology frontiersin.org et al, 2002) or food surfaces with crevices or cracks (Song and Kang, 2022). However, it is important to note that no initial a w values of the black peppercorn were reported, and their methods indicate that inoculated samples were dried for 1 h in a biosafety hood with no mention of the stability of the Salmonella population.…”
Section: Figurementioning
confidence: 99%
“…The improvement of seed germination could also be applicable to lucerne sprout production for human nutrition where various seed treatments have also been investigated, such as the plant immunity modulator (PIM) [47], vacuumed hydrogen peroxide vapor and vacuumed dry heat [48], non-thermal plasma treatment [49], ozone treatment [50], or ozone and electrolyzed water treatment [51]. It can be assumed that there are more potential approaches for the improvement of seeds; however, there is a lack of systematic research comparing the efficacy of the above-mentioned methods on lucerne performance, especially under field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Physical treatments such as heat, high pressure, and irradiation can be effective but can also negatively affect alfalfa seed germination depending on the parameters used [ 16 , 17 , 18 ]. Recent research combining physical and chemical treatments has used dry heat and 2% hydrogen peroxide or vacuumed hydrogen peroxide vapor with vacuumed dry heat to inactivate Salmonella Typhimurium on alfalfa seeds without negatively affecting germination [ 19 , 20 ]. Dry heat and 2% hydrogen peroxide can reduce Salmonella Typhimurium populations on alfalfa seeds by 1.66–3.60 log CFU/g, but long treatment times of up to 24 h may be undesirable [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dry heat and 2% hydrogen peroxide can reduce Salmonella Typhimurium populations on alfalfa seeds by 1.66–3.60 log CFU/g, but long treatment times of up to 24 h may be undesirable [ 19 ]. Vacuumed dry heat at 73 °C and 30% vacuumed hydrogen peroxide vapor were shown to reduce Salmonella Typhimurium to <1 log CFU/g on alfalfa seeds; however, treatment times still required 120 min [ 20 ].…”
Section: Introductionmentioning
confidence: 99%